Pemahaman Peserta Didik Tentang Mandat Budaya Dalam Kejadian 1:28 Terhadap Kepedulian Lingkungan - Hapsarini, Deslana Roidja; Pige, Yendri Wati (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
Abstract Lack of awareness in maintaining the environment should continue to be pursued in providing understanding to students because it is also a human responsibility to maintain the environment in accordance with cultural mandates. Using a descriptive qualitative method with a literature study approach, it can be concluded that environmental care can be measured from four indicators, namely: throwing garbage in its place, maintaining class cleanliness, maintaining school yard cleanliness, and maintaining bathroom cleanliness. Students' understanding of the cultural mandate in incident 1:28 can affect environmental awareness. If students' understanding of the cultural mandate in Genesis 1:28 is taught to students, it will grow students' awareness of the environment at school and at home. Based on the conclusions drawn, it can be said that students' understanding of the cultural mandate in incident 1:28 is very important to encourage students to care about the environment. Therefore, it is better for teachers or parents to teach the cultural mandate in Genesis 1:28 to students so that those who understand the cultural mandate have concern for the environment wherever they are.   Abstrak Kurangnya kesadaran dalam memelihara lingkungan hidup patut terus diupayakan dalam memberi pemahaman kepada peserta didik sebab hal itu juga menjadi tanggung jawab manusia untuk memelihara lingkungan sesuai dengan mandat budaya. Menggunkan metode kualitatif deskriptif dengan pendekatan studi literatur dapat disimpulkan bahwa kepedulian lingkungan dapat diukur dari empat indikator, yaitu: membuang sampah pada tempatnya, menjaga kebersihan kelas, menjaga kebersihan halaman sekolah, dan menjaga kebersihan kamar mandi. Pemahaman siswa tentang mandat budaya dalam Kejadian 1:28 dapat mempengaruhi kepedulian lingkungan. Jika pemahaman peserta didik tentang mandat budaya dalam Kejadian 1:28 diajarkan kepada peserta didik maka akan menumbuhkan kepedulian peserta didik terhadap lingkungan di sekolah maupun di rumah. Berdasarkan kesimpulan yang ditarik, dapat dikatakan bahwa pemahaman peserta didik tentang mandat budaya dalam Kejadian 1:28 sangat penting untuk mendorong peserta didik agar peduli terhadap lingkungan.  Oleh kerena itu, sebaiknya guru atau orang tua harus mengajarkan mandat budaya dalam Kejadian 1:28 kepada peserta didik sehingga mereka yang memahami tentang mandat budaya memiliki kepedulian terhadap lingkungan di manapun mereka berada.